Synergistic Efficacy of the Combination of Co Q10 and α-tocopherol Against Arsenic Induced Hepatotoxicity in Sprague Dawley Rats - Mir, Urfa Zaryab; Rashid, Amir; Javad Yousaf, Muhammad; Gul Khan, Hammad; Mir, Amaidah; Laique, Talha (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Millions of the people around the world are exposed to higher levels of arsenic via contaminated drinking water which is a threat to human and animal life. Aim: To determine the possible beneficial effects of co Q10 and tocopherol against arsenic induced liver damage in Sprague Dawley rats. Methodology: In this randomized controlled trial Group I was given standard rat diet with distilled water. Groups II, III, IV and V were administered arsenic 5mg/L mixed in distilled water ad libitum. Additionally, group III and group IV were administered co Q10 and tocopherol 250 mg/kg mixed in rat diet. Group V was given both co Q10 and tocopherol 125 mg/kg each mixed in rat diet. The experiment continued for 15 days. At the end of the intervention, serum was extracted to measure serum LFTs on micro lab. SPSS version 23.0 was used to analyze the data. Results: There was a significant (p ≤ 0.05) rise of serum ALT, AST and ALP after arsenic administration in group II animals. Treatment with co Q10 and tocopherol reduced the levels of serum LFTs (p ≤ 0.05) in group III and IV animals respectively. Whereas, the synergistic effects of both these natural antioxidants in group V animals, reversed these changes to control values. Conclusion: We concluded that the synergistic effects of both co Q10 and tocopherol were better than their individual effects against arsenic induced hepatotoxicity.